Drug addiction - Romero Villagrán, Cesar (Revista Universidad de Guayaquil, 2009)
Drugs are substances whose consumption can lead to dependence, stimulation, or depression of the central nervous system. From a scientific point of view, the term 'drug' refers to the active ingredient or raw material. In the medical field, a drug is synonymous with a pharmaceutical. However, from a social perspective, drugs are prohibited and harmful substances to health, the abuse of which generates both individual and social harm.Drug addiction is a disease that has its origin in the brains of a large number of human beings. It is characterized by its chronicity or long duration, its progression, and relapses.
Keywords: Drugs; Narcotics